Method for synthesizing nano-composite electrocatalyst with heterostructure through pulse laser induction and application of nano-composite electrocatalyst

The synthesis of CuS@SnO2 nanocomposite electrocatalysts is solved by pulsed laser induced, and the problem of low accumulation and conversion efficiency of solid lithium carbonate in lithium-carbon dioxide batteries is achieved, efficient carbon dioxide reduction performance and cycle stability of lithium-carbon dioxide batteries are achieved, and the Preparation cost and energy consumption, suitable for large-scale production.

CN119140120APending Publication Date: 2024-12-17BOHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411281572.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing lithium-carbon dioxide batteries have problems such as solid lithium carbonate accumulation, low conversion efficiency, and high reactive oxygen or hydrogen monoxide production in side reactions, which limits their application. The preparation process of tin-based electrocatalysts is complex and costly, making it difficult to produce on a large scale. .

Method used

CuS@SnO2 nanocomposite electrocatalyst was prepared by pulsed laser induced synthesis method. Through the molar ratio control of copper, sulfur and tin sources, combined with cationic surfactant and ultrasonic stirring, photothermal induction was used to form heterogeneity using femtosecond laser. The catalyst of structure.

Benefits of technology

It achieves efficient carbon dioxide reduction formic acid production performance, improves the cycle stability and specific capacity of lithium-carbon dioxide batteries, reduces preparation costs and energy consumption, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140120A_ABST
    Figure CN119140120A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalyst preparation methods, and relates to a method for synthesizing a nano-composite electrocatalyst with a heterostructure through pulse laser induction and application of the nano-composite electrocatalyst. According to the invention, the electrocatalyst with more exposed effective active sites can be obtained by optimizing the pulse energy and using the time-shaped laser two sub-pulse sequences. The preparation method is simple in synthesis, short in time consumption, low in energy consumption and good in dispersity, and the heterostructure nano composite electrocatalyst has excellent carbon dioxide reduction performance and can be used for preparing a cathode electrocatalyst of a lithium-carbon dioxide battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalyst preparation methods, and relates to a method for synthesizing a nanocomposite electrocatalyst with a heterogeneous structure by pulsed laser induction and application thereof. Background Art

[0002] With the growth of the global economy, the demand for energy continues to rise, which in turn promotes the development and utilization of energy, and inevitably leads to a continuous increase in CO2 emissions. In order to effectively respond to this environmental challenge, electrocatalytic CO2 reduction (CO2RR) technology came into being. In addition, lithium-carbon dioxide batteries have become a new research hotspot due to their dual advantages of carbon dioxide conversion and energy storage capacity. However, the lithium-carbon dioxide batteries reported so far mainly use lithium carbonate and amorphous carbon as discharge products, which will bring a series of problems: first, solid lithium carbonate continues to accumulate during the discharge process, resulting in positive electrode passivation; second, the conversion efficiency between wide-bandgap insulating lithium carbonate and carbon dioxide during the cycle is low, resulting in increased battery polarization and poor energy efficiency; third, the side reactions during the decomposition of lithium carbonate will produce highly active O2 or 1 O2, they will participate in battery reactions in subsequent cycles, thus affecting the battery life and limiting the practical application of lithium-carbon dioxide batteries.

[0003] Tin (Sn)-based electrocatalysts have become a hot topic of interest due to their low price, environmental friendliness, strong catalytic ability, and high selectivity for formic acid. However, the oxide itself has disadvantages such as poor conductivity and difficulty in exposing active sites. If it is prepared as a nanocomposite electrocatalyst with a heterogeneous structure, it can have a better interfacial charge distribution and the synergistic effect between different active sites can promote the reaction kinetics. At present, a variety of synthesis methods have been tried, such as evaporation, oxidation, and sol-gel methods. However, these synthesis methods generally have problems such as complex preparation process, high cost, unsuitable for large-scale production, and affecting the performance of the catalyst.

[0004] Converting CO2 into economically valuable chemical raw materials, such as formic acid and carbon monoxide, can not only alleviate CO2 emissions, but also provide valuable chemical raw materials for industrial production, which is of great significance to the sustainable development of mankind. HCOOH Generally, it can reach about 90%, but this technology can not only convert CO2 into fuels and chemicals, but also help to achieve renewable energy storage.

[0005] Therefore, it is of great practical significance to develop a laser-induced synthesized electrocatalyst with a heterostructure for application in carbon dioxide reduction to produce formic acid and as a cathode material for lithium-carbon dioxide batteries. Summary of the invention

[0006] In view of the above-mentioned technical problems, the present invention provides a method and application of pulse laser induced synthesis of heterogeneous structure nanocomposite electrocatalyst. The present invention is simple to synthesize, short in time, low in energy consumption, good in dispersibility, and the heterogeneous structure nanocomposite electrocatalyst has excellent carbon dioxide reduction performance, and the electrocatalyst can be used as a cathode electrocatalyst for lithium-carbon dioxide batteries.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows.

[0008] A method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure comprises the following steps: Step 1, adding a copper source and a sulfur source to ultrapure water in sequence, stirring evenly, adding a cationic surfactant, further stirring evenly, adding a tin source, ultrasonically stirring, and then obtaining a mixed solution; Step 2: Subsequently, the mixture of step 1 was laser irradiated with a pulse energy of 250 ± 20 mW and a pulse delay of 5 to 15 ps, and then passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h. The obtained material was washed with distilled water and ethanol for further purification to obtain an electrocatalyst precursor; Step 3. Finally, the electrocatalyst precursor obtained in step 2 is vacuum dried overnight, and further ground to obtain a CuS@SnO2 electrocatalyst, i.e., a nanocomposite electrocatalyst with a heterogeneous structure.

[0009] Furthermore, in step 1, the molar ratio of the sulfur source, the copper source and the tin source is 5:2:(3-7).

[0010] Furthermore, in step 1, the copper source is one of copper chloride dihydrate, copper chloride or copper sulfate, preferably copper chloride dihydrate; the sulfur source is one of thiourea, L-cysteine ​​or ammonium thiocyanate, preferably thiourea; the cationic surfactant is one of hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride or benzoic acid, preferably hexadecyltrimethylammonium bromide; the tin source is one of stannous chloride, tin dioxide or stannous sulfate, preferably stannous chloride.

[0011] Furthermore, in step 1, the stirring time is 30 to 40 min.

[0012] Furthermore, in step 2, during laser irradiation, the molar volume ratio of the sulfur source to the ultrapure water is 0.130-0.140 mol·L -1 .

[0013] Furthermore, in step 2, the laser irradiation time is 1.5 to 2.5 h.

[0014] Furthermore, in step 2, the centrifugal speed is 8000-12000 rpm and the time is 5-8 min.

[0015] Furthermore, in step 2, during washing, the mixture is washed with distilled water for 2 to 3 times, and then washed with ethanol for 2 to 3 times.

[0016] Furthermore, in step 3, during vacuum drying, the drying temperature is 60±10° C. and the drying time is 10 to 12 h.

[0017] The electrocatalyst prepared as described above is used as a carbon dioxide reduction electrocatalyst and a lithium carbon dioxide battery cathode electrocatalyst.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows.

[0019] (1) The SnO2 nanoparticles in the synthesized CuS@SnO2 heterostructure electrocatalyst are well modified on the surface of CuS nanosheets, which makes the catalyst have a large specific surface area, which is beneficial to the exposure of active sites and promotes the COOH - The formation of key intermediates has more effective electron transfer, thereby improving the activity of CO2RR and the selectivity for formic acid; the materials prepared by this method (heterostructured nanocomposite electrocatalysts) have FE for the reduction of carbon dioxide to formic acid HCOOH It is 80~95%.

[0020] (2) Femtosecond lasers with ultrashort pulse duration and femtosecond peak power density have unique characteristics, which can instantly cool the processing solution and rapidly solidify the prepared material. Moreover, the duration of ultrashort pulses is shorter than the characteristic time scale of most physical and chemical processes, resulting in chemical reaction pathways and chemically selective molecular excitations that can be effectively controlled by lasers. Based on this, the present invention relates to a green, one-step controllable method, which achieves the regulation of chemical reactions by laser ablation of precursor solutions, synthesizes nanoscale CuS@SnO2 catalysts, and controls photothermally induced reduction / oxidation by adjusting laser energy and pulse delay to optimize the catalytic activity of the catalyst. In addition, electrocatalysts with various morphologies were synthesized by changing the pulse energy and pulse delay. Catalysts with more exposed effective active sites can be obtained by optimizing the pulse energy and using a time-shaped laser two-sub-pulse sequence. The proposed method is environmentally friendly and does not require high vacuum treatment, high temperature treatment, or a series of cumbersome operations.

[0021] (3) The CuS@SnO2 electrocatalyst of the present invention exhibits excellent electrocatalytic activity in the production of formic acid in CO2RR. The CuS@SnO2 electrocatalyst is used as a cathode electrocatalyst for lithium-carbon dioxide batteries and also exhibits high specific capacity and excellent cycle stability. The assembled lithium-carbon dioxide battery has a specific capacity of 0.2 mA·cm-2 At a current density of 0.1 mA·cm, 176 stable cycles can be achieved. -2 At a current density of 5361 mAh g -1 The discharge specific capacity of the electrocatalyst is very good, and the electrocatalyst has a very good application prospect as a cathode catalyst for lithium-carbon dioxide batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a process flow chart of the present invention (corresponding to Example 1).

[0023] Figure 2 This is a SEM image of the CuS@SnO2 heterojunction electrocatalyst of the present invention (corresponding to Example 1).

[0024] Figure 3 TEM image of the CuS@SnO2 heterojunction electrocatalyst of the present invention (corresponding to Example 1).

[0025] Figure 4 HRTEM image of the CuS@SnO2 heterojunction electrocatalyst of the present invention (corresponding to Example 1).

[0026] Figure 5 The LSV curve of the CuS@SnO2 heterojunction electrocatalyst of the present invention (corresponding to Example 1); the electrolyte solution is: 1 mol·L -1 KOH; the scan rate of LSV test is: 0.1 V·s -1 .

[0027] Figure 6 The CuS@SnO2 heterojunction electrocatalyst of the present invention (corresponding to Example 1) is used as the cathode electrocatalyst of the Li-CO2 battery at a current density of 0.1 mA·cm -2 The first discharge curve below.

[0028] Figure 7 The cycle performance curve of the CuS@SnO2 heterojunction electrocatalyst of the present invention (corresponding to Example 1) as the cathode electrocatalyst of the Li-CO2 battery; the current density is 0.2 mA·cm -2 , the capacity limit is 500 mAh g -1 .

[0029] Figure 8 This is a Faraday efficiency diagram of CO2RR at different potentials for the CuS@SnO2 heterojunction electrocatalyst of the present invention (corresponding to Example 1).

[0030] Fig. 9 This is the SEM image of CuS@SnO2 of the present invention (corresponding to Example 2).

[0031] Fig.10 This is the LSV curve of CuS@SnO2 of the present invention (corresponding to Example 2); the electrolyte solution is: 1 mol·L - 1 KOH; the scan rate of LSV test is: 0.1 V·s -1 .

[0032] Fig.11 This is a Faraday efficiency diagram of CO2RR of CuS@SnO2 at different potentials according to the present invention (corresponding to Example 2).

[0033] Fig.12 This is the SEM image of CuS@SnO2 of the present invention (corresponding to Example 1).

[0034] Fig.13 LSV curve of CuS@SnO2 of the present invention (corresponding to Example 1); the electrolyte solution is: 1 mol·L - 1 KOH; the scan rate of LSV test is: 0.1 V·s -1 .

[0035] Fig.14 This is the Faraday efficiency diagram of CO2RR of CuS@SnO2 at different potentials of the present invention (corresponding to Example 1).

[0036] Fig.15 This is the SEM image of CuS@SnO2 of the present invention (corresponding to Example 2).

[0037] Fig.16 This is the LSV curve of CuS@SnO2 of the present invention (corresponding to Example 2); the electrolyte solution is: 1 mol·L - 1 KOH; the scan rate of LSV test is: 0.1 V·s -1 .

[0038] Fig.17 This is the Faraday efficiency diagram of CO2RR of CuS@SnO2 of the present invention (corresponding to Example 2) at different potentials.

[0039] Fig.18 This is the SEM image of CuS@SnO2 of the present invention (corresponding to Example 3).

[0040] Fig.19 This is the LSV curve of CuS@SnO2 of the present invention (corresponding to Example 3); the electrolyte solution is: 1 mol·L - 1 KOH; the scan rate of LSV test is: 0.1 V·s -1 .

[0041] Fig. 20 This is the Faraday efficiency diagram of CO2RR of CuS@SnO2 at different potentials of the present invention (corresponding to Example 3).

[0042] Fig.21 This is the SEM image of CuS@SnO2 of the present invention (corresponding to Example 4).

[0043] Fig. 22 LSV curve of CuS@SnO2 of the present invention (corresponding to Example 4); the electrolyte solution is: 1 mol·L - 1 KOH; the scan rate of LSV test is: 0.1 V·s -1 .

[0044] Fig.23 This is the Faraday efficiency diagram of CO2RR of CuS@SnO2 at different potentials of the present invention (corresponding to Example 4).

[0045] Fig.24 This is the SEM image of CuS@SnO2 of the present invention (corresponding to Example 5).

[0046] Fig.25 This is the LSV curve of CuS@SnO2 of the present invention (corresponding to Example 5); the electrolyte solution is: 1 mol·L - 1 KOH; the scan rate of LSV test is: 0.1 V·s -1 .

[0047] Fig.26 This is the Faraday efficiency diagram of CO2RR of CuS@SnO2 at different potentials of the present invention (corresponding to Example 5). DETAILED DESCRIPTION

[0048] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0049] A method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure comprises the following steps: Step 1, adding a copper source and a sulfur source to ultrapure water in sequence, stirring evenly, adding a cationic surfactant, further stirring evenly, adding a tin source, ultrasonically stirring, and stirring for 30 to 40 minutes to obtain a mixture; Step 2, then, the mixture of step 1 was laser irradiated for 1.5-2.5 h with a pulse energy of 250±20 mW and a pulse delay of 5-15 ps, and then passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h, and the obtained material was washed with distilled water and ethanol successively (washed with distilled water 2-3 times, washed with ethanol 2-3 times) to further purify, and obtain an electrocatalyst precursor; Step 3. Finally, the electrocatalyst precursor obtained in step 2 is vacuum dried overnight at 60±10°C for 10-12 h, and further ground to obtain a CuS@SnO2 electrocatalyst, i.e., a nanocomposite electrocatalyst with a heterogeneous structure.

[0050] Furthermore, in step 1, the molar ratio of the sulfur source, the copper source and the tin source is 5:2:(3-7).

[0051] Furthermore, in step 1, the copper source is one of copper chloride dihydrate, copper chloride or copper sulfate, preferably copper chloride dihydrate; the sulfur source is one of thiourea, L-cysteine ​​or ammonium thiocyanate, preferably thiourea; the cationic surfactant is one of hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride or benzoic acid, preferably hexadecyltrimethylammonium bromide; the tin source is one of stannous chloride, tin dioxide or stannous sulfate, preferably stannous chloride.

[0052] Furthermore, in step 2, during laser irradiation, the molar volume ratio of the sulfur source to the ultrapure water is 0.130-0.140 mol·L -1 .

[0053] Furthermore, in step 2, the centrifugal speed is 8000-12000 rpm and the time is 5-8 min.

[0054] Example 1.

[0055] 0.1364 g of copper chloride dihydrate (CuCl2·2H2O) and 0.1522 g of thiourea (CH4N2S) were added to 15 mL of ultrapure water in sequence, stirred for 1 h, 0.0364 g of hexadecyltrimethylammonium bromide (CTAB) was added, stirred for 30 min, 0.3617 g of stannous chloride (SnCl2) was added, ultrasonicated for 5 min, and stirred for another 30 min. The resulting solution was laser irradiated for 2 h at a pulse energy of 250 mV and a pulse delay of 10 ps. After the mixture was cooled to room temperature, it was passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h. Then, the product was centrifuged, washed with distilled water and ethanol for further purification, and then vacuum dried at 60 ° C for 10 h, and further ground to obtain a CuS@SnO2 electrocatalyst with a heterogeneous structure.

[0056] The scanning electron microscope image of the CuS@SnO2 heterojunction electrocatalyst prepared in Example 1 of the present invention is as follows: Figure 2 As shown, it can be observed that SnO2 nanoparticles are uniformly attached to the surface of CuS nanosheets.

[0057] The transmission electron microscopy image of the CuS@SnO2 heterojunction electrocatalyst prepared in Example 1 of the present invention is as follows: Figure 3 As shown, it can be clearly seen that the two particles are closely connected together, and it can be preliminarily determined that this electrocatalyst is a heterogeneous structure.

[0058] The high magnification transmission electron microscopy image of the CuS@SnO2 heterojunction electrocatalyst prepared in Example 1 of the present invention is as follows: Figure 4 As shown, two clear and obvious lattice fringes can be seen, and the lattice spacings of 0.32 and 0.26 nm correspond to the (101) crystal plane of CuS and the (101) crystal plane of SnO2, respectively, which proves that the CuS@SnO2 electrocatalyst is a heterogeneous structure.

[0059] The LSV curve of the CuS@SnO2 heterojunction electrocatalyst prepared in Example 1 of the present invention is as follows: Figure 5 As shown, at the maximum FE HCOOH The efficiency corresponds to a voltage at which the current density can reach -292 mA·cm -2 , it has the highest current density and higher efficiency in reducing carbon dioxide compared to other electrocatalysts.

[0060] The Faraday efficiency of the CuS@SnO2 heterojunction electrocatalyst prepared in Example 1 of the present invention for carbon dioxide reduction at different potentials is as follows: Figure 6 As shown in the figure, it can be seen that CuS@SnO2 exhibits excellent electrocatalytic performance for CO2 reduction to produce HCOOH, and at a voltage of -1.1 V FE HCOOH Reaching a maximum value of 94.9%.

[0061] The first discharge curve measured by assembling the battery according to Example 1 is as follows: Figure 7 As shown, at 0.1 mA·cm -2 At a current density of 5361 mAh g -1 The discharge capacity.

[0062] The cycle performance curve of the battery assembled according to Example 1 is as follows: Figure 8 As shown, at a current density of 0.2 mA·cm -2 And the specific capacity is limited to 500 mAh g -1 Under these circumstances, the CuS@SnO2 heterojunction electrocatalyst can achieve 176 stable cycles.

[0063] Example 2.

[0064] 0.1364 g of copper chloride dihydrate (CuCl2·2H2O) and 0.1522 g of thiourea (CH4N2S) were added to 15 mL of ultrapure water in sequence, stirred for 1 h, 0.0364 g of hexadecyltrimethylammonium bromide (CTAB) was added, stirred for 30 min, 0.2411 g of stannous chloride (SnCl2) was added, ultrasonicated for 5 min, and stirred for another 30 min. The resulting solution was laser irradiated for 2 h at a pulse energy of 250 mV and a pulse delay of 10 ps. After the mixture was cooled to room temperature, it was passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h. Then, the product was centrifuged, washed with distilled water and ethanol for further purification, and then vacuum dried at 60 ° C for 10 h, and further ground into powder to obtain the CuS@SnO2 electrocatalyst.

[0065] The scanning electron microscope image of the CuS@SnO2 electrocatalyst prepared in Example 2 of the present invention is as follows: Fig. 9 As shown, CuS nanoparticles are well loaded on the surface of SnO2 nanosheets, but the nanoparticles show slight agglomeration.

[0066] The LSV curve of the CuS@SnO2 electrocatalyst prepared in Example 2 of the present invention is as follows: Fig.10 As shown, at the maximum FE HCOOH The efficiency can reach -256 mA·cm at the corresponding voltage -2 The current density is better than the maximum current density that can be achieved by most existing electrocatalysts.

[0067] The Faraday efficiency of the CuS@SnO2 electrocatalyst prepared in Example 2 of the present invention for carbon dioxide reduction at different potentials is as follows: Fig.11 As shown in the figure, it can be seen that CuS@SnO2 exhibits excellent electrocatalytic CO2 reduction to produce HCOOH performance, and at a voltage of -1.1 V FE HCOOH Reaching a maximum value of 80.4%.

[0068] Comparative example 1.

[0069] 0.1364 g of copper chloride dihydrate (CuCl2·2H2O) and 0.1522 g of thiourea (CH4N2S) were added to 15 mL of ultrapure water in sequence, stirred for 1 h, 0.0364 g of hexadecyltrimethylammonium bromide (CTAB) was added, stirred for 30 min, 0.3617 g of stannous chloride (SnCl2) was added, ultrasonicated for 5 min, and stirred for another 30 min. The resulting solution was laser irradiated for 2 h at a pulse energy of 300 mV and a pulse delay of 10 ps. After the mixture was cooled to room temperature, it was passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h. Then, the product was centrifuged, washed with distilled water and ethanol for further purification, and then vacuum dried at 60 ° C for 10 h, and further ground into powder to obtain the CuS@SnO2 electrocatalyst.

[0070] The scanning electron microscope image of the CuS@SnO2 electrocatalyst prepared in Comparative Example 1 of the present invention is as follows: Fig.12 As shown, the morphology is that of spherical accumulation of materials and aggregation occurs.

[0071] The LSV curve of the CuS@SnO2 electrocatalyst prepared in Comparative Example 1 of the present invention is as follows: Fig.13 As shown, at the maximum FE HCOOH The efficiency can only reach -65 mA·cm at the corresponding voltage -2 of current density.

[0072] The Faraday efficiency of the CuS@SnO2 electrocatalyst for carbon dioxide reduction at different potentials prepared in Comparative Example 1 of the present invention is as follows: Fig.14 As shown in the figure, it can be seen that the electrocatalytic performance of the CuS@SnO2 electrocatalyst prepared under this condition for CO2 reduction to produce HCOOH is poor. HCOOH Only 50.9%.

[0073] Comparative example 2.

[0074] 0.1364 g of copper chloride dihydrate (CuCl2·2H2O) and 0.1522 g of thiourea (CH4N2S) were added to 15 mL of ultrapure water in sequence, stirred for 1 h, 0.0364 g of hexadecyltrimethylammonium bromide (CTAB) was added, stirred for 30 min, 0.3617 g of stannous chloride (SnCl2) was added, ultrasonicated for 5 min, and stirred for another 30 min. The resulting solution was laser irradiated for 2 h at a pulse energy of 200 mV and a pulse delay of 10 ps. After the mixture was cooled to room temperature, it was passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h. Then, the product was centrifuged, washed with distilled water and ethanol for further purification, and then vacuum dried at 60 ° C for 10 h, and further ground into powder to obtain the CuS@SnO2 electrocatalyst.

[0075] The scanning electron microscope image of the CuS@SnO2 electrocatalyst prepared in Comparative Example 2 of the present invention is as follows: Fig.15 As shown in the figure, it can be observed that the spherical materials are accumulated and serious adhesion occurs.

[0076] The LSV curve of the CuS@SnO2 electrocatalyst prepared in Comparative Example 2 of the present invention is as follows: Fig.16 As shown, at the maximum FE HCOOH The current density that can be achieved at the corresponding voltage is about -166 mA·cm -2 .

[0077] The Faraday efficiency of the CuS@SnO2 electrocatalyst for carbon dioxide reduction at different potentials prepared in Comparative Example 2 of the present invention is as follows: Fig.17 As shown, it can be seen that the electrocatalytic performance of CuS@SnO2 in CO2 reduction to produce HCOOH prepared under this condition is poor, and the FEHCOOH is only 68.9% at a voltage of -1.1V.

[0078] Comparative example 3.

[0079] 0.1364 g copper chloride dihydrate (CuCl2·2H2O) and 0.1522 g thiourea (CH4N2S) were added to 15 mL ultrapure water in sequence, stirred for 1 h, 0.0364 g hexadecyltrimethylammonium bromide (CTAB) was added, stirred for 30 min, 0.3617 g stannous chloride (SnCl2) was added, ultrasonicated for 5 min, stirred for another 30 min, and the resulting solution was laser irradiated for 2 h at a pulse energy of 250 mV and a pulse delay of 0 ps. After the mixture was cooled to room temperature, it was passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h. Then, the product was centrifuged, washed with distilled water and ethanol for further purification, and then vacuum dried at 60 ° C for 10 h and ground into powder to obtain the CuS@SnO2 electrocatalyst.

[0080] The scanning electron microscope image of the CuS@SnO2 electrocatalyst prepared in Comparative Example 3 of the present invention is as follows: Fig.18 As shown, SnO2 nanoparticles agglomerated on the surface of CuS nanosheets.

[0081] The LSV curve of the CuS@SnO2 electrocatalyst prepared in Comparative Example 3 of the present invention is as follows: Fig.19 As shown, at the maximum FE HCOOH The efficiency can reach -228mA·cm at the corresponding voltage -2 of current density.

[0082] The Faraday efficiency of the CuS@SnO2 electrocatalyst for carbon dioxide reduction at different potentials prepared in Comparative Example 3 of the present invention is as follows: Fig. 20 As shown, it can be seen that the electrocatalytic CO2 reduction to HCOOH performance of the CuS@SnO2 electrocatalyst prepared under this condition is significantly worse than that of the CuS@SnO2 heterojunction electrocatalyst prepared in Example 1. HCOOH Only 75.7%.

[0083] Comparative example 4.

[0084] 0.1364 g of copper chloride dihydrate (CuCl2·2H2O) and 0.1522 g of thiourea (CH4N2S) were added to 15 mL of ultrapure water in sequence, stirred for 1 h, 0.0364 g of hexadecyltrimethylammonium bromide (CTAB) was added, stirred for 30 min, 0.1206 g of stannous chloride (SnCl2) was added, ultrasonicated for 5 min, and stirred for another 30 min. The resulting solution was laser irradiated for 2 h at a pulse energy of 250 mV and a pulse delay of 10 ps. After the mixture was cooled to room temperature, it was passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h. Then, the product was centrifuged, washed with distilled water and ethanol for further purification, and then vacuum dried at 60 ° C for 10 h, and further ground into powder to obtain the CuS@SnO2 electrocatalyst.

[0085] The scanning electron microscope image of the CuS@SnO2 electrocatalyst prepared in Comparative Example 4 of the present invention is as follows: Fig.21 As shown, particles are piled up and aggregated.

[0086] The LSV curve of the CuS@SnO2 electrocatalyst prepared in Comparative Example 4 of the present invention is as follows: Fig. 22 As shown, at the maximum FE HCOOH The current density at the voltage corresponding to the efficiency can only reach -79 mA·cm -2 , indicating that the electrocatalyst has poor performance in reducing carbon dioxide.

[0087] The Faraday efficiency of the CuS@SnO2 electrocatalyst for carbon dioxide reduction at different potentials prepared in Comparative Example 4 of the present invention is as follows: Fig.23 As shown, it can be seen that the electrocatalytic performance of the CuS@SnO2 electrocatalyst prepared at this ratio for CO2 reduction to produce HCOOH is poor compared to that of the embodiment. HCOOH Only 39.3%.

[0088] Comparative Example 5.

[0089] 0.1364 g copper chloride dihydrate (CuCl2·2H2O) and 0.1522 g thiourea (CH4N2S) were added to 15 mL ultrapure water in sequence, stirred for 1 h, 0.0364 g hexadecyltrimethylammonium bromide (CTAB) was added, stirred for 30 min, 0.4822 g stannous chloride (SnCl2) was added, ultrasonicated for 5 min, and stirred for another 30 min. The resulting solution was laser irradiated for 2 h at a pulse energy of 250 mV and a pulse delay of 10 ps. After the mixture was cooled to room temperature, it was passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h. Then, the product was centrifuged, washed with distilled water and ethanol for further purification, and then vacuum dried at 60 ° C for 10 h, and further ground into powder to obtain the CuS@SnO2 electrocatalyst.

[0090] The scanning electron microscope image of the CuS@SnO2 electrocatalyst prepared in Comparative Example 5 of the present invention is as follows: Fig.24 As shown, the spherical substances are sticky and unevenly distributed.

[0091] The LSV curve of the CuS@SnO2 electrocatalyst prepared in Comparative Example 5 of the present invention is as follows: Fig.25 As shown, at the maximum FE HCOOH The current density under the efficiency corresponding voltage can reach -237 mA·cm -2 , and its maximum current density is less than the maximum current density that can be achieved by the electrocatalysts prepared in Examples 1 and 2.

[0092] The Faraday efficiency of the CuS@SnO2 electrocatalyst for carbon dioxide reduction at different potentials prepared in Comparative Example 5 of the present invention is as follows: Fig.26 As shown in the figure, it can be seen that CuS@SnO2 has the performance of electrocatalytic CO2 reduction to produce HCOOH. At a voltage of -1.1 V, FE HCOOH Reached 75.7%.

[0093] The instruments used in the tests in the above embodiments and comparative examples are as follows.

[0094] 1. Scanning electron microscopy (SEM, Hitachi S-4800) was used to characterize the morphology of the electrocatalysts.

[0095] 2. Transmission electron microscopy (TEM) characterization was performed using a Talos F200S G2 at 220 kV.

[0096] 3. Laser irradiation was performed using a sapphire laser system (Spectra Physics Inc.).

[0097] 4. All electrochemical tests were performed on a CHI760D electrochemical workstation (Shanghai Chenhua).

[0098] All potentials in this paper were calibrated to the reversible hydrogen electrode (RHE) according to the Nernst equation (E(V vs. RHE) = E(V vs. Hg / HgO) + 0.098 V + 0.059 × pH).

[0099] Laser irradiation preparation of electrocatalyst operation process: A sapphire laser system (Spectra Physics Inc.) was used to generate linearly polarized laser pulses with a pulse duration of 50 fs (full width at half maximum) at a central wavelength of 800 nm and a repetition rate of 1 kHz. Each pulse was split into two temporally separated sub-pulses using a Michelson interferometer, resulting in a double-pulse irradiation with two pulse characteristics almost identical. The time interval ranged from 100 fs to tens of ps, which was adjusted by a computer-controlled linear translation stage with micrometer resolution. Before irradiation, the precursor solution was filled into a glass container mounted on a computer-controlled six-axis positioning system (M-840.5DG, PI, Inc.), and the solution was continuously moved during laser irradiation. The laser beam was normally focused inside the solution by a plano-convex lens. CuS@SnO2 electrocatalysts were prepared using femtosecond laser single pulses (energy range 100~600 mW) and double pulses (total energy range 200~300 mW). The intensity ratio of the two sub-pulses is 1.01:1, and the pulse delay between the two sub-pulses is 5~15 ps. The pulse energy is precisely controlled by a half-wave plate and a polarizer installed before the entrance of the interferometer. The preparation is carried out in air at ambient pressure and temperature.

[0100] In summary, the present invention has developed an electrocatalyst with a heterogeneous structure synthesized by laser induction and used as a carbon dioxide reduction to produce formic acid and a high-performance Li-CO2 battery cathode catalyst to achieve efficient electrocatalytic activity. The CuS@SnO2 electrocatalyst of the present invention has a more excellent CO2RR performance and high selectivity for formic acid. At the same time, CuS@SnO2 as a Li-CO2 battery cathode electrocatalyst has a current density of 0.2 mA·cm -2 176 stable cycles can be achieved at 0.1 mA·cm -2 At a current density of 2.5 2.5 mAh·g, CuS@SnO2 has a high capacity of 5361 mAh·g -1The discharge specific capacity of the battery is 2.487 W. The novel synthesis method proposed in the present invention, i.e., the method of inducing the synthesis of electrocatalysts by direct laser irradiation of precursor solutions, has the advantages of being fast, simple, green and pollution-free. The synthesized CuS@SnO2 electrocatalyst with a heterostructure provides ideas for the design and preparation of high-performance Li-CO2 batteries. And preliminary test results show that the prepared electrocatalyst is a promising carbon dioxide reduction electrocatalyst that can be used in the production of formic acid. This work provides a new strategy for coupling the functions of various transition metal compounds to construct heterostructured electrocatalysts, and also promotes its application in fields such as energy conversion and storage.

[0101] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure, characterized in that: The steps include: Step 1, adding a copper source and a sulfur source to ultrapure water in sequence, stirring evenly, adding a cationic surfactant, further stirring evenly, adding a tin source, performing ultrasonic stirring, and obtaining a mixture; Step 2, then, the mixture of step 1 was laser irradiated with a pulse energy of 250±20 mW and a pulse delay of 5-15 ps, and then passed through a dialysis membrane with a molecular weight cutoff of 1 kDa for 24 h, and the obtained material was washed with distilled water and ethanol for further purification to obtain an electrocatalyst precursor; Step 3. Finally, the electrocatalyst precursor obtained in step 2 is vacuum dried overnight, and further ground to obtain a CuS@SnO2 electrocatalyst, i.e., a nanocomposite electrocatalyst with a heterogeneous structure.

2. The method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure according to claim 1, characterized in that: In the step 1, the molar ratio of the sulfur source, the copper source and the tin source is 5:2:(3-7).

3. The method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure according to claim 1, characterized in that: In step 1, the copper source is one of copper chloride dihydrate, copper chloride or copper sulfate; the sulfur source is one of thiourea, L-cysteine ​​or ammonium thiocyanate; the cationic surfactant is one of hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride or benzoic acid; the tin source is one of stannous chloride, tin dioxide or stannous sulfate.

4. The method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure according to claim 1, characterized in that: In the step 1, the stirring time is 30 to 40 minutes.

5. The method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure according to claim 1, characterized in that: In step 2, during laser irradiation, the molar volume ratio of the sulfur source to the ultrapure water is 0.130-0.140 mol·L -1 .

6. The method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure according to claim 1, characterized in that: In step 2, the irradiation time is 1.5 to 2.5 h.

7. The method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure according to claim 1, characterized in that: In step 2, the centrifugal speed is 8000-12000 rpm and the time is 5-8 min.

8. The method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure according to claim 1, characterized in that: In step 2, during washing, the sample is washed with distilled water for 2-3 times, and then washed with ethanol for 2-3 times.

9. The method for laser-induced synthesis of a nanocomposite electrocatalyst having a heterogeneous structure according to claim 1, characterized in that: In the step 3, during vacuum drying, the drying temperature is 60±10° C. and the drying time is 10 to 12 h.

10. A catalyst prepared by the method for laser-induced synthesis of a nanocomposite electrocatalyst with a heterogeneous structure according to any one of claims 1 to 9 as a carbon dioxide reduction electrocatalyst and a cathode electrocatalyst for a lithium carbon dioxide battery.